PENEGAKAN HUKUM PIDANA TERHADAP PENIPUAN TIKET KONSER ONLINE COLDPLAY MELALUI MEDIA JASTIP (JASA TITIP) - Johansen Burton Bisuk (2024)
information that are developing very rapidly and rapidly. This phenomenon occurs in all parts of the world, regardless of developed or developing countries. As a world community, a country is required to follow developments in technology and information, so that it can compete in a global world that is increasingly modern, practical, and efficient. Entrustment services are one of the business ideas that are currently popular in online businesses. Entrustment services are known or abbreviated as Jastip, jastip is an informal service provided by sellers for consumers to obtain an item that they want to buy for their needs or desires but cannot go to the place where the item is sold or have not had time to buy the item directly so that someone uses a consignment service. Juridically, in response to the rise of crime through electronic media, the government has issued Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions. This research uses a normative juridical research type. To understand and explain how law enforcement is against criminal acts of Coldplay online concert ticket fraud by jastip media (entrustment services). The legal regulations for the criminal act of online concert ticket fraud are contained in Article 28 paragraph (1) in conjunction with Article 45A paragraph (1) of the ITE Law, as well as in the Criminal Code in Article 378. By the provisions of the laws in force in Indonesia. There are steps or efforts to enforce criminal law against online concert ticket fraud through jastip media, namely repressive and preventive law enforcement.